أثر القيادة الإدارية على تنمية المهارات لدى المورد البشري - يسرى, رعدي; مريم الباتول, حمية (unuversity of eloued- جامعة الوادي, 2023)
تهدف هذه الدراسة إلى معرفة "أثر القيادة الإدارية على تنمية المهارات لدى المورد البشري" وتمت الدراسة الميدانية بمؤسسة سونلغاز -وحدة تقرت-، واعتمدنا على المنهج الوصفي التحليلي للتحقق من تأثير المتغير المستقل المتمثل في أبعاد القيادة الإدارية (التنظيم، الاتصال، صناعة القرار، بناء فريق العمل، تحفيز العاملين، الإشراف، المتابعة والتقويم)، على المتغير التابع تنمية المهارات المورد البشري المتعلقة بموضوع البحث، ولتحقيق هذا الهدف اعتمدت الدراسة على الاستبيان كأداة لجمع البيانات، وتم توزيع 90 استمارة استبيان على الموظفين بالمؤسسة محل الدراسة وتم الدراسة على 84 استمارة، ولتحليل هذه البيانات قد اعتمدنا على برنامج (SPSS) من خلال استخدام بعض الأساليب الإحصائية لفرضيات الدراسة وتساؤلاتها، وقد توصلت الدراسة إلى أنه يوجد مستوى مرتفع لتنمية المهارات في المؤسسة محل الدراسة بتأثير أبعاد القيادة الإدارية عليها من وجهة نظر العمال. This study aims to learn about the "impact of management leadership on the development of skills in the human resource". The field study was conducted at SONLGAS, and we relied on the analytical descriptive curriculum to verify the impact of the independent variable of management leadership dimensions. (Organization, communication, decision-making, team building, motivation of workers, supervision, follow-up and evaluation) For this purpose, the study relied on the questionnaire as a tool for data collection, 90 questionnaires were distributed to the staff of the institution in question and 84 forms were examined. (SPSS) through the use of some statistical methods for the hypotheses and questions of the study, the study found that there is a high level of skills development in the institution being studied with the impact of administrative leadership dimensions on it from the workers' point of view.
Keywords: القيادة الإدارية، الأبعاد القيادة، تنمية المهارة، المهارات لدى المورد البشري.; management leadership, leadership dimensions, skill development, human resource skills.